2021
DOI: 10.3390/vaccines9091012
|View full text |Cite
|
Sign up to set email alerts
|

New 1,2,3-Triazole Scaffold Schiff Bases as Potential Anti-COVID-19: Design, Synthesis, DFT-Molecular Docking, and Cytotoxicity Aspects

Abstract: Schiff bases encompassing a 1,2,3-triazole motif were synthesized using an efficient multi-step synthesis. The formations of targeted Schiff base ligands were confirmed by different spectroscopic techniques (FT-IR, 1H NMR, 13C NMR, and CHN analysis). The spectral data analysis revealed that the newly designed hydrazones exist as a mixture of trans-E and cis-E diastereomers. Densityfunctional theory calculations (DFT) for the Schiff bases showed that the trans-trans form has the lowest energy structure with max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…1,2,3-triazole–based Schiff bases 64 ( Supplementary Figure S7 ) showed considerable binding affinities (−7.4 to −9.1 kcal/mol) with 7BQY, indicating their potential prospect as therapeutics for COVID-19 ( Supplementary Figure S7 ) ( Said et al, 2021 ).…”
Section: Therapeutic Applicationmentioning
confidence: 99%
“…1,2,3-triazole–based Schiff bases 64 ( Supplementary Figure S7 ) showed considerable binding affinities (−7.4 to −9.1 kcal/mol) with 7BQY, indicating their potential prospect as therapeutics for COVID-19 ( Supplementary Figure S7 ) ( Said et al, 2021 ).…”
Section: Therapeutic Applicationmentioning
confidence: 99%
“…Moreover, several drugs on the market, such as rufinamide (anticonvulsant), cetirizine (antibiotic), and tazobactam (antibacterial agent) have inserted a 1,2,3 triazole core into their framework [24] (Figure 1). In the literature, there are numerous 1,2,3-triazoles tethered to bioactive heterocyclic moieties, such as (Figure 2A-D), that have been documented as promising antitubercular agents [25][26][27][28][29][30][31]. In particular, the 1,4-disubstituted 1,2,3-triazole derivatives were identified and proven to have high efficacy against Mycobacterium tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the phenoxy methyl moiety in the development of the new candidate with significant antimycobacterium activity is represented by the lead structure (Figure 3B), which exerts its activity through inhibition of the enoyl-acyl carrier protein reductase InhA enzyme, IC50 = 0.38 µM [33]. In the literature, there are numerous 1,2,3-triazoles tethered to bioactive heterocyclic moieties, such as (Figure 2A-D), that have been documented as promising antitubercular agents [25][26][27][28][29][30][31]. In particular, the 1,4-disubstituted 1,2,3-triazole derivatives were identified and proven to have high efficacy against Mycobacterium tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey revealed that 1,2,3 triazole derivatives may act as potential inhibitors against Covid -19 proteins. [19,20] In the current study, three 1,2,3 triazole derivatives, namely, (E)-1-(1-benzyl-5-methyl-4,5-dihydro-1H-1,2,3-triazol-4-yl)-3-phenylprop-2-en-1-one (BMTPP), (E)-1-(1-benzyl-5-methyl-4,5-dihydro-1H-1,2,3-triazol-4-yl)-3-(p-tolyl) prop-2-en-1-one(BMTTP) and (E)-1-(1-benzyl-5-methyl-4,5-dihydro-1H-1,2,3-triazol-4-yl)-3-(4-isopropylphenyl) prop-2-en-1-one (BMTIP) were synthesized and their drug-likeness has been evaluated. The single crystal X-ray diffraction studies have been investigated for compound 2.…”
mentioning
confidence: 99%